POETIC (Program for Enhanced Training in Cancer): An Initial Experience of Supporting Capacity Building for Oncology Training in Sub‐Saharan Africa. (10th June 2019) - Fish, Madeleine; Parkes, Jeannette; Dharsee, Nazima; Dryden‐Peterson, Scott; Efstathiou, Jason; Schnipper, Lowell; Chabner, Bruce A.; Parikh, Aparna R.
Abstract: Background: Sub‐Saharan Africa is simultaneously facing a rising incidence of cancer and a dearth of medical professionals because of insufficient training numbers and emigration, creating a growing shortage of cancer care. To combat this, Massachusetts General Hospital and Beth Israel Deaconess Medical Center partnered with institutions in South Africa, Tanzania, and Rwanda to develop a fellowship exchange program to supplement the training of African oncologists practicing in their home countries. Methods: In its initial year, 2018, the Program for Enhanced Training in Cancer (POETIC) hosted a pilot cohort of seven fellows for 3‐week observerships in their areas of interest. Researchers distributed questionnaires for program evaluation to participants prior to arrival and upon departure; additionally, three participated in semistructured interviews. Results: Five themes emerged from the qualitative data: expectations of POETIC, differences between oncology in the U.S. and in sub‐Saharan Africa, positive elements of the program, areas for improvement, and potential impact. Fellows identified several elements of Western health care that will inform their practice: patient‐centered care; clinical trials; and collaboration among medical, radiation, and surgical oncologists. From the quantitative data, feedback was primarily around logistical areas for improvement. Conclusion: POETIC was found to be feasible and valuable. The results from the pilot year justify the program's continuation in hopes of strengthening global health partnerships to support oncology training in Africa. One weakness is the small number of fellows, which will limit the impact of the study and the relevance of its conclusions. Future research will report on the expansion of the program and follow‐up with former participants. Implications for Practice: This work presents a novel model for fellowship exchange between lower‐ and higher‐resourced areas. The program is a short‐term observership with tumor boards and didactic teaching sessions incorporated. By attracting oncologists who aim to practice in their home countries, it facilitates international collaboration without contributing to the preexisting lack of medical professionals in low‐ and middle‐income countries. Abstract : This brief communication presents case reports for two patients with metastatic melanoma treated with empiric BRAF and MEK inhibitors.